2011
DOI: 10.1007/s12306-011-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute true trigger wrist following partial extensor carpi radialis brevis tendon rupture

Abstract: Triggering in association with movements of the wrist or "true trigger wrist" due to the extensor tendon is rare. There are only few case reports in literature, but none were associated with the acute partial tendon rupture. We present a case of true trigger wrist originating from partial rupture of extensor carpi radialis brevis tendon (ECRB). In contrast to the other reports, the interval between an initial injury and development of triggering was short because the partial tendon rupture was bunching and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…[2] (Table 1), our case belongs to type A (caused by a tumor). When we reviewed the literature, we found that triggering at the wrist may also have been the result of other causes such as partial flexor [8] or extensor [9] tendon laceration, and other mechanical causes [10], [11]. All these causes may occur in the pediatric age group and hence, an extended classification may be offered (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[2] (Table 1), our case belongs to type A (caused by a tumor). When we reviewed the literature, we found that triggering at the wrist may also have been the result of other causes such as partial flexor [8] or extensor [9] tendon laceration, and other mechanical causes [10], [11]. All these causes may occur in the pediatric age group and hence, an extended classification may be offered (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Anomalous muscles (Type B and C) are usually associated with a bulge in the distal forearm which is more apparent on passive hyper-extension of the wrist [2]. A history of a laceration is suggestive of type D [8], [9], while a history of carpal tunnel release is suggestive of Type E [10], [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, the snapping wrist has been considered a condition in which movement of the wrist or fingers leads to the triggering of the wrist. However, in 1986, Desai et al (67) proposed to use the term trigger wrist to indicate triggering which occurs following the movement of the wrist and not that of the fingers (68). This is true trigger wrist while the condition in which triggering at the wrist is associated with finger movements would be more appropriately described as trigger finger at the wrist (6).…”
Section: Definition and Clinical Signsmentioning
confidence: 99%